Socio-Cultural Implications of China’s Belt Road Initiative into Pakistan - Lee Keng Ng; Balbir Bhasin; Ahmad Rahal; Jim Beard (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2020)
China has embarked on its massive infrastructure development projects across and through its western neighbors, including the China-Pakistan Economic Corridor. This grants China quick access to the Arabian Sea and alleviates its strategic security concerns regarding its vulnerability to the “Malacca dilemma.” This also improves Pakistan’s economic aspects of job creation, infrastructure development, and technology transfer. The differences between the economic prospects and the societal values of the two nations are bound to raise tensions and conflicts. China is a secular country with a culture of homogeneity, aggressiveness, task-orientation, discipline, perseverance, intolerance of others, risk-taking, long term orientation, competition and superiority. Pakistan on the other hand, is deeply rooted in the Islamic religion, lackadaisical, less-disciplined, less focused, passive, short-term oriented and easygoing. This paper evaluates the implications and pitfalls for both countries to avoid for mutual benefits